Characteristic performance customer relation management: a case study technology education instituition in Malaysia / Muhamad Fairos Mohamad Shah - Mohamad Shah, Muhamad Fairos (Universiti Teknologi MARA, Kedah, 2021)
Customer relationship management (CRM) is a term that refers to practices, strategies and technologies that companies use to manage and analyze customer interactions beside data throughout the customer life cycle with the goal of improving business relationships with customers.Customer relationship management (CRM) assisting in customer retention and driving sales growth for their sustainability.This studied report that problem on customer loyalty is defined as a result of consistently positive emotional experiences which are based on satisfaction and perceive value of a product or services.CRM systems are designed to compile information on customers across different channels or points of contact between the customer and the company which include the company's platform website, telephone, live chat, direct mail, marketing materials and social media. Therefore this study found that CRM technology systems can also give customer satisfaction on facing staff detailed information on customers' personal information, purchase history, buying preferences and concerns.In addition purpose and objective of this study to investigate customer relation management between student intention in organization education and technology platform.The methodological study is basic research and exploratory.In addition sample size and scope of this study is individual student in instituiton organization.Last but not least for conclusion,this study show student satisfaction and loyalty are strongly significant.Further more implication of this study customer intention is highly expected to education organization of body